IMPLEMENTATION OF INTEGRATED MARKETING COMMUNICATIONS IN THE HOSPITALITY INDUSTRY: A LITERATURE REVIEW - Ņikadimovs, Oļegs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The hospitality industry is one of the most dynamic and competitive sectors, it has become more important to communicate marketing messages that are clear, unified and integral throughout all the communication channels to the target audiences. The paper aims to review the previously conducted research efforts on implementation of the concept of integrated marketing communications (IMC) in the hospitality industry. The aim of this research study is to collect and analyse the main concepts and conclusions of theoretical and practical research in the hospitality IMC implementation in the recent years. The methodology for paper selection was the following: 1) databases - Scopus, ScienceDirect, EBSCOHost, Emerald Insight - were examined; 2) main search criterion was “IMC hospitality implementation”, 3). additional research criteria were time of publication and peer-reviewed papers. Qualitative data analysis methods were used to assess the selected papers, while the review itself can be classified as narrative. Eight papers were selected for the analysis, showing an overview of the latest trends in research on IMC implementation in the hospitality industry. The findings indicated correlation between IMC strategy implementation and the impact on target audiences.  This literature review can be used as the theoretical background for future researches.